Effect of Alternative Wood Species and First Thinning Wood on Oriented Strand Board Performance - Fabiane Salles Ferro; Amós Magalhães Souza; Isabella Imakawa de Araujo; Milena Maria Van Der Neut de Almeida; André Luis Christoforo; Francisco Antonio Rocco Lahr (Advances in Materials Science and Engineering)
This study aimed to evaluate the feasibility of using and influence of alternative wood species such as Cambará, Paricá, Pinus, and wood from first thinning operations on oriented strand board (OSB) physical and mechanical properties. Besides that, an alternative resin, castor oil-based polyurethane, was used to bond the particles, due to the better environmental performance when compared to other resins commonly used worldwide in OSB production. Physical properties such as the moisture content, thickness swelling, and water absorption, both after 2 and 24 hours of water immersion, and mechanical properties such as the modulus of elasticity and resistance in static bending, in major and minor axes, and internal bonding were investigated. All tests were performed according to European code EN 300:2006. Results showed the influence of wood species on physical and mechanical properties. Panels made with higher density woods such as Cambará presented better physical performance, while those made with lower density woods such as Pinus presented better mechanical properties. Besides that, strand particle geometry was also influenced on all physical and mechanical properties investigated. Therefore, the feasibility of using alternative species and wood from first thinning and with castor oil-based polyurethane resin in OSB production was verified.